Emotional disturbance of children in need of special education visual impairment - Magiman, Mohamad Maulana; Nordin, Mohd Norazmi; Wan, Mei Qi; Maidin, Siti Sarah; Bahadin, Siti Azura; Mohd Noor, Nor Adila; Abbas, Mohd Saleh (African Science Publications, 2024)
Compared to changes that occur externally such as behavior, internal changes including a person's emotions appear as aspects that are more difficult to detect. In other words, emotional disorders in students with special educational needs are less often surveyed compared to their behavioral problems. Indeed, emotional disturbances in students have a significant impact on themselves as well as other individuals in a class. In general, the American Psychological Association (APA) defines emotion as a complex response pattern that involves elements of experience, behavior and physiology where emotions can bring physical and psychological changes that affect thinking and behavior. Therefore, emotions can appear as information to guide how a person interacts with the world through restricting or broadening behavior based on the situation. Directly, obstacles that appear in the emotional development of children in the form of emotional disorders affect them both externally and internally.